The SmartAG partner: CCAFS East Africa Bi-Annual Newsletter, July - December 2019 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
We are pleased to share with you our SmartAg Partner bi-annual newsletter, highlighting policy engagement, ongoing research, field updates and activities with partners from the second half of 2019.